Osteoprotegerin, RANK and RANKL are not modified by acute exercise in elite rugby players - Banfi, G.; Corsi, M. M.; Galliera, E. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: The OPG-RANK-RANKL system is a new family of bone metabolism biomarkers belonging to the immune system. In this study, were evaluated these biomarkers in professional rugby players after a single-bout of training session. METHODS: The study has been performed on 30 professional male rugby players during a training camp of the Italian National Team, in July, before the start of the competitive season. Blood drawings were performed before and after training in the same day. Levels of soluble OPG, RANKL RANK in serum specimens were measured by commercially available according to the manufacturers` protocols. RESULTS: All the bone markers examined displayed no significative changes after training session. CONCLUSION: Short exercise is insufficient for modifying serum concentrations of these osteoimmunologic markers, as previously indicated for commonly used bone metabolism markers. Future studies will be conducted over an entire competition season in order to define a common profile of bone markers in rugby players.